THE IMPACT OF HEALTH EDUCATION THROUGH VIDEO MEDIA ON PREGNANT WOMEN'S KNOWLEDGE OF EXCLUSIVE BREASTFEEDING IN THE THIRD TRIMESTER - Munawarah, Raudhatul; Keya, Tuestin Apriyanti (Siklus : Journal Research Midwifery Politeknik Tegal, 2025)
Infants who are not exclusively breastfed are more susceptible to intestinal disorders, diarrhoea, upper respiratory tract infections (URTIs), and breast cancer in moms. Mother's understanding of exclusive breastfeeding is an important factor that influences it. Therefore, health education through videos for third trimester pregnant women can increase their knowledge and prepare them for childbirth and breastfeeding. The purpose of this study was to determine the effect of health education with video on the knowledge of third trimester pregnant women about Exclusive Breastfeeding. The design of this study was a quasi-experiment with a one group pretest-posttest design. The study was conducted from April to May 2024 at the Senen District Health Center with 59 pregnant women as respondents who were taken by purposive sampling. Data analysis used the Kolmogorov Smirnov and Wilcoxon Tests. According to the study's findings, one-third of the participants had inadequate knowledge of exclusive breastfeeding prior to receiving health education on the topic. Respondents' knowledge increased (sufficient and good) after exclusive breastfeeding education intervention. Health professionals can effectively educate the public and pregnant women about health issues by using media such as video.